2016
DOI: 10.1158/1541-7786.mcr-15-0207-t
|View full text |Cite
|
Sign up to set email alerts
|

Depleting Tumor-NQO1 Potentiates Anoikis and Inhibits Growth of NSCLC

Abstract: The fundamental role that NAD(P)H/quinone oxidoreductase 1 (NQO1) plays, in normal cells, as a cyto-protective enzyme guarding against stress induced by reactive oxygen species (ROS) is well documented. However, what is not known is whether the observed overexpression of NQO1 in neoplastic cells contributes to their survival. The current study discovered that depleting NQO1 expression in A549 and H292 lung adenocarcinoma cells caused an increase in ROS formation, inhibited anchorage-independent growth, increas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 46 publications
2
47
0
Order By: Relevance
“…Although NQO1 knockdown potentiated anoikis in non-small cell cancer cells (33), manipulation of the levels of NCF2/p67PHOX, ALOX15, FAT4 and NQO1 produced no significant change in ROS in our cells (data not shown). GRHL2 also down-regulated Glutamate Dehydrogenase 1 (GDH1 or GLUD1), an enzyme implicated in the suppression of ROS (27).…”
Section: Resultsmentioning
confidence: 74%
“…Although NQO1 knockdown potentiated anoikis in non-small cell cancer cells (33), manipulation of the levels of NCF2/p67PHOX, ALOX15, FAT4 and NQO1 produced no significant change in ROS in our cells (data not shown). GRHL2 also down-regulated Glutamate Dehydrogenase 1 (GDH1 or GLUD1), an enzyme implicated in the suppression of ROS (27).…”
Section: Resultsmentioning
confidence: 74%
“…However, a large number of studies demonstrated strong up‐regulation of Nqo1 in various cancers such as breast, pancreas, liver, bladder, ovary, thyroid, colorectal, cholangiocarcinoma, uterine cervical cancer, melanoma, and lung cancer . Moreover, Nqo1‐KD inhibited proliferation of cholangiocarcinoma and adenocarcinoma cells . Conversely, Nqo1‐OE increased the proliferation of melanoma cells, suggesting that Nqo1 may function as an oncogene and promote cell proliferation and/or survival of certain cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…(15)(16)(17)(18)(19) Moreover, Nqo1-KD inhibited proliferation of cholangiocarcinoma and adenocarcinoma cells. (38,39) Conversely, Nqo1-OE increased the proliferation of melanoma cells, (40) suggesting that Nqo1 may function as an oncogene and promote cell proliferation and/or survival of certain cancer cells. Additionally, increased expression of Nqo1 protein was correlated with tumor size, advanced clinical stage, and decreased patient survival rates in breast, liver, and lung cancers, (17,19,20) signifying that Nqo1 may also be involved in the progression of certain cancers.…”
Section: Discussionmentioning
confidence: 99%
“…NAD(P)H:quinone oxidoreductase 1 (NQO1) expression is an exploitable, tumor‐specific target for pancreatic cancer therapies. Elevated NQO1 expression is noted in many early forms of cancers such as in pancreatic intraepithelial neoplasia (PanINs), prostatic intraepithelial neoplasia, and breast ductal carcinoma in situ and further increase in this enzyme occurs as these cancers progress . NQO1 bioactivatable drugs are a unique class of rare quinones that include ß‐lapachone (ß‐lap), and deoxynyboquinones .…”
Section: Introductionmentioning
confidence: 99%
“…1). 6,7,10,11 Concomitant NQO1 overexpression and loss of catalase are a hallmark of many solid cancers. NQO1 is over-expressed in >85% of resected pancreatic cancer samples and is preferentially expressed in pancreatic cancer versus, non-cancer, adjacent pancreas.…”
Section: Introductionmentioning
confidence: 99%